Stellaria media (L.) Vill. (common chickweed) - strong or weak competitor in the autumn and early-spring sown crops? - Pacanoski, Zvonko (Acta herbologica, 2024)
Because of its ability to produce large numbers of seeds under cool temperatures, S. media rapidly colonizes any cool, moist area before winter or spring crops can become competitive. It is most commonly a weed in many crops in temperate and subarctic climates, where it is often one of the ﬁrst weeds to appear in spring. S. media is one of the most common weeds in spring and winter cereal stands, the most frequent weed in winter oilseed and peas, highly competitive weed in seedling alfalfa, serious weed in citrus, one of the prevailing weeds in strawberry, and one of the most frequent weed species present in conventional sugar beet. It is a principal weed problem in vegetable production and in gardens and turf in almost every country in temperate part of the world.From the other side, in comparative trials of weed competition and yield suppression in many crops, S. media was found to be less competitive than Avena fatua, Alopecurus myosuroides, Raphanus raphanistrum, Polygonum persicaria, Chenopodium album, Galium aparine and many others weeds. In trials in autumn and early-spring sown crops and established crop plants, such as established alfalfa, S. media was found to be minor competitors, unless present at high densities. The actual competitive effect and associated yield reduction caused by S. media will depend on a number of factors, including time of emergence in relation to the crop. S. media displays vigorous early growth and will cause the greatest yield losses when it emerges at the same time or before the crop. It is also a highly plastic species, meaning that early establishment and resource capture will result in larger more competitive individuals.
Keywords: Stellaria media, crops, weeds, competitor